Sharing the Gospel with [Non-Christian] Students and the Task of Academic Faith Integration - Kaak, Paul (Christian higher education, 2024)
The gospel is central to life in the Christian community. It is formational to the church proper and to the pedagogical task of faith-based colleges and universities. The gospel is also significant for the education of non/nominal Christians who are present in our classrooms. This article describes the gospel as indispensable for faith-based teaching and learning, but perhaps in surprising ways. The focus of this article is “gospel teaching” in classes where the topic is not explicitly religious and when students are present who do not share our Christian convictions. Practical recommendations are made throughout the article and at its close.